A study of herniotomy alone in young adults with uncomplicated indirect inguinal hernia in Hospital Seberang Jaya, Pulau Pinang - Salleh, Syahrul Anuar (2016)
Background: Options of surgery are still controversial in young adults with uncomplicated indirect inguinal hernia. The purpose of this study is to evaluate outcomes of herniotomy in young adults with uncomplicated indirect inguinal hernias. Methods: This is a retrospective cross-sectional study of case record of patients aged between 15 and 34 years old who were diagnosed to have uncomplicated indirect inguinal hernia and underwent herniotomy in Hospital Seberang Jaya, Pulau Pinang. There are 3 aspects of outcome of the surgery in which are postoperative haematoma, chronic pain and recurrence are taken into account. Results were analyzed using desriptive analysis method. Results: A total of 117 patients aged between 15 and 34 years (Mean 23.8 ± 5.5 years), comprising 108 males and 9 females with a male:female ratio of 12:1. Majority were Malays (65.8%) followed by foreigners (22.2%). Majority had no medical history (92.3%) or surgical history (88%) and non-smoker (69.2%). Mean duration of swelling and pain before presentation was 1653.5 ± 2263.9 days and 94.98 ± 323.79 days, respectively. Majority of hernia was right-sided hernia (59.8%). 79.5% of surgery was performed under local anaesthesia and 80.34% was done as day-case surgery. Mean duration surgery was 46.38 ± 21.5 minutes. Content of hernial sac was mostly empty (72.6%). There were postoperative haematoma and recurrence occurred in 5 % and 2%of cases, respectively. There was no chronic pain. Conclusion: Herniotomy alone is sufficient in treating young adults with uncomplicated indirect inguinal hernia in term of postoperative haematoma, chronic pain and recurrence compared to other types of procedure. Moreover it can also provide extra advantages in term of manpower, duration of surgery, hospital stay, total cost of hospitalization and early recovery.